The Profile of Erysipelas and Cellulitis Patients - Ryski Meilia Novarina; Sawitri Sawitri (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2015)
Background: Erysipelas and cellulitis are acute infectious serious skin diseases, due to the entry of bacteria through the unintact skin barrier and can be fatal. Purpose: To determine the clinical manifestation and management of hospitalized erysipelas and cellulitis patients at the dermatolovenerology inpatient Dr. Soetomo General Hospital in period of 2008-2011. Methods: The study was conducted retrospectively based on the medical records of the hospitalized patients include case number, gender, age, main complaint and duration, trigger factors, concomitant factors that can be as the underlying disease, lesion site, laboratory examinations, treatments, length of treatment associated with Erythrocyte Sedimentation Rate (ESR) and the prognosis. Results: The erysipelas and cellulitis cases were 65 cases (1.9%) of the total hospitalized cases of skin diseases, with the number of men and women were 36 and 29 patient, respectively. The highest age group were 45-65 years (35.4%). Main complaint was swelling, redness and pain (66,2%) and the duration of complaints 1-7 days (81.5%), Most triggering factors due to scratching (34%). Anemia (30,8%) is the most underlying disease. The majority of lesion sites are in the lower extremities in 56 patients (86.1%). Laboratory tests showed anemic (30.8%), leukocytosis (44.6%) and (76.9%) ESR > 20mm/h (76.9%). The specimen of the lesion of 18 cases were cultured, there were found majority bacterial were Staphylococcus aureus (37.5%). The managements of treatment of 25 cases (38.5%) were consisted: immobilization, intravenous injection of Ampicillin and wet dressing with normal saline, 15 cases with ESR>50mm/h were treated for 8 -14days. The complications (gangrenosum cellulitis) were found in 1 case (1,5%), and 40 patients (61.5%) discharge from hospital in a recovery state. Conclusion: The management of patients with erysipelas and cellulitis had been appropriate based on the diagnosis and treatment guidelines. Staphylococcus aureus is the most frequent bacteria found in culture.Key words: erysipelas, cellulitis, Staphylococcus aureus.